The Gravity Model of Migration: The Successful Comeback of an Ageing Superstar in Regional Science - Jacques Poot; Omoniyi Alimi; Michael P. Cameron; Dave C. Maré (Institute for the Study of Labor (IZA), 2016)
For at least half a century, and building on observations first made a century earlier, the gravity model has been the most commonly-used paradigm for understanding gross migration flows between regions. This model owes its success to, firstly, its intuitive consistency with migration theories; secondly, ease of estimation in its simplest form; and, thirdly, goodness of fit in most applications. While fitting gravity models of aggregate migration flows started taking backstage to microdata analysis in the 1980s, a recent comeback has resulted from increasing applications to international migration and from the emergence of statistical theories appropriate for studying spatial interaction. In this paper we review the status quo and argue for greater integration of internal and international migration modelling. Additionally we revisit the issues of parameter stability and distance deterrence measurement by means of a New Zealand case study. We argue that gravity modelling of migration has a promising future in a multi-regional stochastic population projection system – an area in which the model has been to date surprisingly underutilised. We conclude with outlining current challenges and opportunities in this field.
Keywords: F22; J61; R23; 330; gravity model; internal migration; international migration; population projection